2017
DOI: 10.1186/s12864-017-3744-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting genome terminus sequences of Bacillus cereus-group bacteriophage using next generation sequencing data

Abstract: BackgroundMost tailed bacteriophages (phages) feature linear dsDNA genomes. Characterizing novel phages requires an understanding of complete genome sequences, including the definition of genome physical ends.ResultWe sequenced 48 Bacillus cereus phage isolates and analyzed Next-generation sequencing (NGS) data to resolve the genome configuration of these novel phages. Most assembled contigs featured reads that mapped to both contig ends and formed circularized contigs. Independent assemblies of 31 nearly iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Our data indicated that linear phage genomes with TDRs were erroneously assembled as CCs. The TDRs are the source of this mis-assembly, which could be corrected by mapping the reads to CCs as described previously [34].…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicated that linear phage genomes with TDRs were erroneously assembled as CCs. The TDRs are the source of this mis-assembly, which could be corrected by mapping the reads to CCs as described previously [34].…”
Section: Resultsmentioning
confidence: 99%
“…A global blastn analysis using the Goe4 genome as query against the non-redundant nucleotide data base of NCBI resulted in the identification of nine closely related virus strains (Juan (MF156577), RadRaab (MF156580.1), Stich (KX349901.1), KonjoTrouble (MF156578.1), Aurora (KX349899.1), QCM11 (KX961631.1) [ 42 ], SerPounce (KY947509.1) [ 43 ], Claudi (KX349900.1) and MG-B1 (KC685370.1) [ 44 ]). Many of those employ B. thuringiesnis as host, but also other members of the B. cereus clade [ 45 ] like B. weihenstephanensis [ 44 ], phage QCM11 in B. anthracis [ 42 ]. Members of this bacterial clade are genomically conserved and mainly differ in number and content of plasmids, which define their lifestyle [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…This procedure can be very time-consuming and contains numerous steps requiring bioinformatic skills, including the installation of the Phamerator program 29 and the management of the related SQL databases. Finally, a concomitant study 30 predicted genome terminus by calculating two criteria, read edge frequencies and neighboring coverage ratio. Finding these procedures heavy and unwieldy for most phage scientists was that motivated us to develop PhageTerm as an easy-to-use program that consolidates into a single straightforward analysis numerous highly-valuable pieces of information about phage termini and packaging mode.…”
Section: Discussionmentioning
confidence: 99%